AB0047 High Soluble IL-7 Receptor Expression in Sjögren's Syndrome Identifies Patients with Increased Immunopathology and Dryness. (15th July 2016) - Hillen, M.R.; Blokland, S.L.; Risselada, A.P.; Bikker, A.; Lauwerys, B.R.; Kruize, A.A.; Radstake, T.R.; van Roon, J.A.
Abstract : Background: Increased expression of interleukin (IL)-7 and its receptor plays a critical role in immunopathology of primary Sjögren's syndrome (pSS). The IL-7/IL-7R axis is involved in formation of (ectopic) lymphoid structures, which is a predictor for lymphoma development in pSS. IL-7 activity is potentiated by the soluble form of its receptor (sIL-7R), which is produced in inflamed tissues by activated stromal cells. Thus, sIL-7R may serve as a biomarker for IL-7-driven activation and lymphoid neogenesis. Objectives: We studied the expression of sIL-7R in pSS in relation to markers of inflammation and saliva production. Methods: 95 pSS patients were diagnosed according to the 2002 criteria. sIL-7R concentration was measured in serum of 68 pSS patients using ELISA and compared to 51 healthy individuals (HC). Labial salivary gland (LSG) biopsy tissues were taken from 27 patients and were incubated in sterile saline for 1 hour at room temperature. sIL-7R was measured using multi-cytokine analysis by Luminex and compared to 24 non-Sjögren's sicca (nSS) patients. Results: Serum levels of sIL-7R were significantly higher in pSS patients compared to healthy controls (median [range]: 610 [52–2201] vs. 294 [58–821] pMol/mL, p=0.0001). pSS patients with sIL-7R levels above those of HC, defined as sIL-7Rhigh, showed markedly increased ESR, serum IgG and lymphocytic focus scores compared to the other pSS patients. Furthermore, sIL-7Rhigh patients had significantly decreased salivary output, as measured by stimulated whole saliva and unstimulated whole saliva (median [range]: 0.2 [0.0–0.9] vs. 1.2 [0.0–4.6] mL/min, p=0.01). In addition, we observed increased sIL-7R production in LSG supernatants from pSS patients compared to nSS. Similar to serum, a sIL-7Rhigh group could be discerned, with higher levels of serum IgG and increased prevalence of ANA, anti-SSA, and anti-SSB autoantibodies (all at least p<0.05). Conclusions: Thus, sIL-7R is increased in serum and LSG supernatant of pSS patients, in which high sIL-7R levels identifies patients with increased markers of inflammation and decreased salivary output. The sIL-7R increase in pSS LSG supernatants indicates that the increased systemic sIL-7R levels are at least partially mediated by local production. High local production of sIL-7R was related to increased B-cell activity and autoimmunity, in line with the described role of IL-7 in lymphoid neogenesis. Disclosure of Interest: None declared